Sosialisasi Manajemen Pakan Ternak Domba di Desa Pesidi, Kecamatan Grabag, Kabupaten Magelang - Sri Hidayati; Della Febriana; Arum Tri Lestari; Farizki Alam; Eka Permana Sakti Irwanto (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Pesidi Village, located in Grabag Subdistrict, Magelang Regency, is a highland region with promising potential in agriculture and livestock, particularly sheep farming. However, one of the major challenges faced by local farmers is the limited availability of forage during the dry season, coupled with the low utilization of agricultural by-products such as rice straw. These constraints often hinder livestock productivity and pose risks to feed security. To address this issue, a community service program was conducted with the aim of introducing and demonstrating local-based feed processing technologies, including silage, ammoniation, and Urea Mineral Block (UMB) production. The activity was implemented in several stages: problem identification, socialization, education, training, and monitoring of farmer implementation. Through this participatory approach, farmers were given hands-on training and practical guidance on processing alternative feed sources to ensure the availability of nutritious and sustainable livestock feed. The results showed that farmers began adopting UMB as a feed supplement due to its practicality and visible benefits in maintaining livestock health and productivity. However, silage and ammoniation methods were not yet widely adopted, mainly due to limited experience, lack of supporting equipment, and the perception that the processes were relatively complex. Despite these challenges, the program succeeded in raising farmer awareness of the importance of feed diversification and the optimization of agricultural waste. The training provided valuable insights into how the integration of silage, ammoniation, and UMB can increase feed efficiency, reduce dependency on fresh forage, and support sustainable livestock management. The implementation of these three technologies holds significant potential to enhance sheep farming productivity in rural highland communities, while simultaneously strengthening food security and supporting environmentally friendly agricultural practices.